Исследование влияния тока накала на параметры плазмы плазмогенератора «пинк»; Известия вузов. Физика; Т. 58, № 9-2 - Ковальский С. С.; Денисов В. В.; Коваль Н. Н. Николай Николаевич; Лопатин И. В. (2015, 2015)
Заглавие с экрана